THE IMPORTANCE OF EDUCATION FOR ORAL HEALTH AWARENESS - Neves de Souza, Kathianna; Neves de Souza Bibiano, Raquel (Health and Society, 2023)
This article seeks to examine the importance of education for oral health awareness. The general objective of this work was to understand the importance of education for oral health hygiene awareness. Even though we carry out many actions and create projects to improve the quality of education in Brazil, we cannot fail to highlight the need for such knowledge for other areas such as, for example, education and oral hygiene in schools. For theorists of this research such as Brasil (2000); Ferreira (2011); Rangel (2017), among others, state that promoting actions and carrying out projects can promote not only the knowledge necessary for prevention and the habit of hygiene and oral health, but there is also the possibility for the student to become a protagonist in this process, being responsible for bringing knowledge to other people in their socio-cultural environment. To carry out this work, bibliographical studies of books, scientific articles, dissertations, magazines and periodicals were carried out. For greater reliability on what was proposed to be researched in this work, a quantitative research will be carried out, through a diagnostic questionnaire composed of 6 (six) questions that will deal with the theme contained in this work, with the research subjects being: teachers, coordinators and public and private school managers in the municipality of Gravatá - PE. Through the results and information taken from the research questionnaires, and the percentages duly collected and measured, it will be possible to understand the importance of projects and actions at school aimed at education in health and oral hygiene. As the data is collected and the percentages presented, it will be possible to check whether there is a possibility that socio-economic and socio-cultural factors are contributing to the lack of health, hygiene and oral health.